Media Events A Critical Contemporary Approach - Mitu, Bianca; Poulakidakos, Stamatis; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Media Events: A Critical Contemporary Approach proposes an interdisciplinary and multicultural approach of Dayan and Katz's theory of media events (1992) by applying it to contemporary situations. The contributing authors come from a range of countries (UK, USA, Mexico, Germany, Finland, Italy, Greece, Portugal, Ukraine) and analyse the theory of media events from different perspectives, incorporating social media and offering a re-positioning of Dayan and Katz's theory of media events. By bringing new perspectives into this field, the proposed volume is an important contribution as it grounds the intervention and rethinking of the theory into further empirical research. This volume has the potential to function as a 'cross-generational' link between one of the 'early classics' of media and communication studies on the one hand and the present generation of researchers on the other.
Keywords: Social Media; Media and Communication; Media Studies; Media Research